Penyuluhan Hukum Pencegahan Tindak Pidana Narkotika dan Bantuan Hukum di Desa Kawahmanuk, Kuningan - Amalya Nurazizah Sofyanti; Davidly Herma Maulana; Intan Santika; Koko Ahmad Faisal; Lutfi Imam Taufik; Regga Rizki Restu Fauzi; Muhammad Beben Bahtiar (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
The spread of narcotics in Indonesia has reached a critical level. Its distribution is expanding and affecting all groups. This phenomenon requires serious handling and mitigation efforts from all elements of society. Therefore, education is needed to increase legal knowledge and understanding through legal counseling for the community, especially the young men and women of Kawahmanuk Village, Darma District, Kuningan Regency, specifically teenagers, regarding the laws and regulations regarding narcotics crimes. This will enable the youth of Kawahmanuk Village to become aware of their behavior to avoid deviant behavior and violations of prohibited acts. They can also actively participate in supporting government programs to understand Law Number 35 of 2009 concerning Narcotics. This activity provides numerous benefits, such as sharing and discussions with legal experts who are knowledgeable about narcotics and target partners to better understand the content and substance of Law Number 35 of 2009 concerning Narcotics, as well as determining policy directions and strategic steps to anticipate, prevent, and combat narcotics use. One effort or step that can be used to minimize the use and distribution of narcotics.